Urbanicity and Disparities in the Functional and Physical Abilities of Older Adults Using the Health and Retirement Study: A Cross-Sectional Study. - Alzahmi, Amal; Covinsky, Kenneth; Ankuda, Claire; Cenzer, Irena (Journal of Applied Gerontology, 2025)
This study investigates disparities between older adults based on urbanicity in the United States. We analyzed data from 8259 participants aged 65+ from the 2018 Health and Retirement Study. The mean age was 74 (SD 8). Low-urbanicity participants (29%) were more likely white (88% vs. 77%, p <.001), and had lower education (20% vs. 16%, p -value =.017), higher rates of hypertension (69% vs. 66.3%, p =.035), lung disease (15% vs. 11%, p =<.001), and cognitive impairment (24% vs. 19%, p <.001). After adjustment for demographics, they were less physically active (60% vs. 55%, p =.021) and more dependent on IADLs (19% vs. 16%, p =.018). Urbanicity significantly affects physical abilities (i.e., jogging, climbing stairs, and handling objects) more in younger participants (65–75) than older ones (75+) (p for interaction =.003,.007, and.012, respectively). Significant urbanicity-based disparities in older adults' physical and functional abilities must be addressed to tailor interventions that improve their quality of life.